Comparison of the Sublingual and Vaginal Misoprostol for Medical Termination of Pregnancy in Cases of First and Second Trimester Abortion: A Quasi Experimental Study - Khan, Umber Imtiaz; Iftikhar, Bushra; Jabeen, Syeda Suraya; Akram, Nuzhat Aisha; Subktageen, Bushra; Fatima, Arwa (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the success rate of sublingual and vaginal Misoprostol for medical termination of pregnancy in the first and second trimesters.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Obstetrics and Gynecology, Combined Military Hospital, Malir Pakistan, from May 2019 to Nov 2019.Methodology: Two hundred patients in their first or second trimester of pregnancy with different indications for termination of pregnancy were included through consecutive sampling. Spousal consent was also taken along with wife consent. Patients were randomly assigned to one of the two groups. Group-A received sublingual Misoprostol 600 mcg stat followed by 400 mcg four hourly and group-B received the same dose of Misoprostol vaginally. The success rate was assessed through complete termination of pregnancy within 72 hours. Age, parity, induction to expulsion interval (IEI) and each patient's medical history was also noted.Results: After 24 hours success rate was 93% in the sublingual group compared to 78% in the vaginal group. After 48 hours sublingual group achieved a 100% success rate compared to 84% in the vaginal group, which was improved to 92% after 72 hours. The difference in success rates of both groups remained significant at 24, 48 and 72 hours IEI (p-value = 0.003, p-value